An Advanced Finite Element Modeling for the Failure of Notched Ceramic Matrix Composite With TFP Patch Reinforcement - Zhao, Gang; Tang, Jianbo; Wang, Jun; Chen, Yunsheng; Feng, Yajie; Chen, Yousi; Xin, Shiqing; Jian, Xigao; Li, Shuxin; Zhang, Shouhai; Xu, Jian (Frontiers in Materials, 2021)
An advanced modeling strategy for notched ceramic matrix composite coupons with patch reinforcement was proposed to investigate the failure mechanisms. This model considered the tailored fiber–placed (TFP) yarn details obtained from the design phase and the embedded element concept which was used to successfully overcome the meshing difficulties. Inter-ply “glue” layers were simulated using the surface-based contact cohesive element method, so the delamination due to interfacial material discontinuity and damage can be well reproduced and analyzed. For composite ply, the energy-based composite progressive damage model that is independent of the mesh size was applied. Virtual test campaign was performed with a variety of geometrical and material parameters, and the damage and failure mechanisms based on the stress analysis can be revealed to support the design optimization of patch reinforcement.